Public Attitudes and Private Prejudices: Assessing Voters’ Willingness to Vote for Out Lesbian and Gay Candidates - Everitt, Joanna; Horvath, Laszlo (Frontiers in Political Science, 2021)
Our study concerns the factors leading to the electoral success and failure of LGBTQ candidates in the context of the changing nature of prejudices. We hypothesize that more positive views toward “respectability candidates,” as captured by familial status, has replaced explicit prejudice toward out LGBTQ candidates in societies where acceptance of sexual minorities in general has grown. In a survey experiment conducted with a sample of Canadian voters, one of the first countries to legalize marriage equality, we find suggestions that voters are more likely to reward lesbian and gay candidates who adopt heteronormative relationships (married with children vs. single) than those who do not. These patterns become more evident when we explore causal heterogeneity with controls for individual-level characteristics and attitudes that typically predict support toward lesbian and gay candidates. Here we find these predictors rewarded single lesbian and gay candidates, whereas lesbian and gay candidates with families were simply more supported across the board.